Os sentidos produzidos nas charges de Henfil no jornal O Pasquim sobre o AI-5 - Pazinato, Cássius Selvero (2021)
The present research, affiliated to the French Pêcheuxtiana discourse analysis, aims to understand how the meanings and discursive memory are constituted in Henfil’s cartoons published in the newspaper O Pasquim under the terms of Institutional Act Number 5 (AI-5), which was in force from 1968 to 1978. For that, among the cartoons published by Henfil in O Pasquim in that period, we selected for analysis discursive clippings referring to some of the themes that were contemplated by the AI-5, such as, for example, the restriction on freedom of expression and the so-called “economic miracle”. From that, we make some observations about the constitution of the historical-discursive process of these materialities from where meanings emerge, provided by the inter-discourse, looking at them, as a social practice, to understand the functioning of the discourse, its relationship with the subjects and with the ideology (ORLANDI, 2005). We try to verify the functioning of the speech in a combination of verbal and non-verbal elements, giving visibility to the ideological aspects, and the production conditions in which the AI-5 sayings are inscribed. Henfil’s cartoons, using humor and irony, produce effects of contesting meanings, making it possible to understand language as space of resistance, mistakes and subjectivity. Our work is divided into four chapters: In the first chapter, we cover the path of the history of the press in Brazil until the emergence of O Pasquim; in chapter two, we explain the history of the Brazilian military dictatorship, emphasizing AI-5, when the newspaper O Pasquim appeared, we also bring the story of Henfil’s professional life; in chapter three we trace a theoretical-methodological path through AD and in chapter four we describe and theoretically problematize our corpus to arrive at the analytical procedure. From the developed study, it was possible to understand that, more than reaching the general objective of the research project, the dissertation work was able to leverage very important political-ideological understanding in the scope of the study of a questioning press and to position graphic humor as a factor that enhances transgression of understanding in readers and symbolic resistance. It is always clear how the cartoon reveals its potential for mobilization and resistance, linked to the publication and its historical context, driven by humor as a constitutive element.